ANALISIS PEMBELAJARAN DARING MATA KULIAH BAHASA INDONESIA DI KELAS RENDAH PADA MAHASISWA PGSD FKIP UNIVERSITAS QUALITY MEDAN - Gemala Widiyarti; Dina Novita; Renata Br. Sitepu (JGK (Jurnal Guru Kita), 2022)
Analysis of Online Learning for Indonesian Language Courses in Low Grades for Pgsd Fkip Students at the University of Quality Medan. The Covid pandemic that hit the world, not only Indonesia, has paralyzed the economic system, trade tourism and of course the world of education. Teachers and students are required to be technologically literate in carrying out teaching and learning activities. With this pandemic, changing the existing learning system in Indonesia from offline learning to online learning. Teaching is one of the main tasks for a teacher, where the teacher is able to convey subject matter to students so that what the child did not know before has changed to know, and those who do not understand understand. Online is connected through computer networks, the internet, and so on. Due to the development of the times during a pandemic like this it is increasingly being expanded. Online is an interaction between someone and someone through conversation, which can be done in student learning activities. with learning from this students can think critically which directs students to be able to solve problems, and students can do this online learning anywhere and anytime, and lecturers can see student posts and provide feedback on assignments from students. This study uses a qualitative descriptive method with observation instruments and field notes.